Application of The Death Penalty to Police Officers in Murder Cases (Cassation Study No. 813 K/Pid/2023) - Giovani Alber; Zainal Abidin Pakpahan; Muhammad Yusuf Siregar (International Journal of Science and Environment (IJSE), 2026)
The background of this article is the phenomenon of strict law enforcement against law enforcement officers themselves, especially in murder cases involving members of the Indonesian National Police. The Supreme Court's Cassation Decision No. 813 K/Pid/2023, which imposed the death penalty on a police officer, is an important precedent to be studied. This article analyzes the effectiveness of the death penalty in this context by considering the defendant's positive contributions in the past. The discussion is conducted through philosophical, juridical, and sociological approaches. The results indicate that the consideration of the defendant's contributions does not automatically negate the unlawful nature of his actions, thus the death penalty is deemed effective as an effort to restore justice and public trust. In conclusion, this decision affirms the principle of equality before the law and functions as a shock therapy for the Police institution.